Enhancing Peace and Security through Ethno - Religious Tolerance in Nigeria for Sustainable Development - Egwuanikwu, Mary Ifechukwude (NIU Journal of Humanities; Vol 8 No 3 (2023): NIU Journal of Humanities, Vol. 8 No. 3, September 2023DO - 10.58709/niujhu.v8i3.1691, 2023)
In recent times, the spate of insecurity through ethno-religious intolerance in Nigeria, a heterogeneous society has become an issue of concern. The paper scrutinized ethnic and religious tolerance as means of fostering peace and security in Nigeria for sustainable development. Peace and Security are germane in the development of every nation; but can only be achieved through tolerance among the ethnic and religious groups. The study employed descriptive and historical methods to elicit information. The significance of peace and security to development; together with the synergy between ethno- religious tolerance, peace and security were discussed. Primary and secondary sources of data collection which includes observation, text books, magazines, journals, and others were consulted in the documentation of the outcome of this research. The findings revealed that ethno-religious tolerance promotes harmony and enabling environment for healthy business operations that enhances growth across all sectors. The paper recommended that the government, religious and community leaders should enlighten the masses on the significance of tolerance, sincere dialogue; reconciliation, among others; which would serve as instruments to uphold peace and douse security challenges currently bedeviling the nation. It therefore behooves on the government to employ the necessary template for good governance embedded in peace and security for development to flourish. Religious leaders should ensure that right religious tenets are taught and practiced in order to discourage religious sentiments or fanaticism. Such would entrench national integration and peaceful co-existence among associates of various ethnic and religious affiliations for ultimate stability and sustainable development.    Keywords: Peace, Security, Ethnicity, Religion, Tolerance, Sustainable Development